Disulfide Crosslinked Hydrogels Made From the Hydra Stinging Cell Protein, Minicollagen-1 - Farajollahi, Sanaz; Dennis, Patrick B.; Crosby, Marquise G.; Slocik, Joseph M.; Pelton, Anthony T.; Hampton, Cheri M.; Drummy, Lawrence F.; Yang, Steven J.; Silberstein, Meredith N.; Gupta, Maneesh K.; Naik, Rajesh R. (Frontiers in Chemistry, 2020)
Minicollagens from cnidarian nematocysts are attractive potential building blocks for the creation of strong, lightweight and tough polymeric materials with the potential for dynamic and reconfigurable crosslinking to modulate functionality. In this study, the Hydra magnipapillata minicollagen-1 isoform was recombinantly expressed in bacteria, and a high throughput purification protocol was developed to generate milligram levels of pure protein without column chromatography. The resulting minicollagen-1 preparation demonstrated spectral properties similar to those observed with collagen and polyproline sequences as well as the ability to self-assemble into oriented fibers and bundles. Photo-crosslinking with Ru(II)(bpy)32+ was used to create robust hydrogels that were analyzed by mechanical testing. Interestingly, the minicollagen-1 hydrogels could be dissolved with reducing agents, indicating that ruthenium-mediated photo-crosslinking was able to induce disulfide metathesis to create the hydrogels. Together, this work is an important first step in creating minicollagen-based materials whose properties can be manipulated through static and reconfigurable post-translational modifications.